Cost savings associated with nutritional support in medical inpatients: an economic model based on data from a systematic review of randomised trials. Issue 7 (9th July 2021) - Schuetz, Philipp; Sulo, Suela; Walzer, Stefan; Vollmer, Lutz; Brunton, Cory; Kaegi-Braun, Nina; Stanga, Zeno; Mueller, Beat; Gomes, Filomena
Abstract : Background and aims: Nutritional support improves clinical outcomes during hospitalisation as well as after discharge. Recently, a systematic review of 27 randomised, controlled trials showed that nutritional support was associated with lower rates of hospital readmissions and improved survival. In the present economic modelling study, we sought to determine whether in-hospital nutritional support would also return economic benefits. Methods: The current economic model applied cost estimates to the outcome results from our recent systematic review of hospitalised patients. In the underlying meta-analysis, a total of 27 trials (n=6803 patients) were included. To calculate the economic impact of nutritional support, a Markov model was developed using transitions between relevant health states. Costs were estimated accounting for length of stay in a general hospital ward, hospital-acquired infections, readmissions and nutritional support. Six-month mortality was also considered. The estimated daily per-patient cost for in-hospital nutrition was US$6.23. Results: Overall costs of care within the model timeframe of 6 months averaged US$63 227 per patient in the intervention group versus US$66 045 in the control group, which corresponds to per patient cost savings of US$2818. These cost savings were mainly due to reduced infection rate and shorter lengths of stay. We also calculated the costs to prevent a hospital-acquired infection and a non-elective readmission, that is, US$820 and US$733, respectively. The incremental cost per life-day gained was −US$1149 with 2.53 additional days. The sensitivity analyses for cost per quality-adjusted life day provided support for the original findings. Conclusions: For medical inpatients who are malnourished or at nutritional risk, our findings showed that in-hospital nutritional support is a cost-effective way to reduce risk for readmissions, lower the frequency of hospital-associated infections, and improve survival rates.